Teachers’ reflections on mathematics teaching practices in a vulnerable context - Páez, David Alfonso; Eudave Muñoz, Daniel; Cañedo Ortiz, Teresa de Jesús; Macías Esparza, Ana Cecilia (Multi-Science Journal, 2020)
The objective of this research is to show the difficulties and the challenges identified by teachers in their mathematics teaching practices. The research is based on the concept of reflection-action, thus a workshop-course centered on collaborative work and on reflections about teaching practices was designed in order to achieve the objective. Ten mathematics teachers the Telebachillerato (Higher Secondary Education Subsystem, Mexico) participated in this research. The results show that teachers have a variety of challenges, but also difficulties, particularly involving getting students to construct knowledge autonomously, as well as teachers selecting and using resources in accordance to the subject matter to be taught. In addition, there is also lack of mathematical and pedagogical knowledge in the participants. Collaborative work is required, leading teachers towards building the necessary knowledge for Higher Secondary Education in order to avoid student obstacles.